Modulation of cellular signaling by herpesvirus-encoded G protein-coupled receptors - de Munnik, Sabrina M.; Smit, Martine J.; Leurs, Rob; Vischer, Henry F. (Frontiers in Pharmacology, 2015)
Human herpesviruses are widespread infectious pathogens that have been associated with proliferative and inflammatory diseases. During viral evolution, human herpesviruses have pirated genes encoding viral G protein-coupled receptors (vGPCRs), which are expressed on infected host cells. These vGPCRs show highest homology to human chemokine receptors, which play a key role in the immune system. Importantly, vGPCRs have acquired unique properties such as constitutive activity and the ability to bind a broad range of human chemokines. This allows vGPCRs to hijack human proteins and modulate cellular signaling for the benefit of the virus, ultimately resulting in immune evasion and viral dissemination to establish a widespread and lifelong infection. Knowledge on the mechanisms by which herpesviruses reprogram cellular signaling might provide insight in the contribution of vGPCRs to viral survival and herpesvirus-associated pathologies.